The moderating effects of theatrical components on the relationship between emotional labor and emotional exhaustion - Dong-Jenn Yang; Tsung-Kuang E. Ma; Sheng-Hsiung Lee (International Journal of Management, Economics and Social Sciences (IJMESS), 2014)
The employees deliver services to customers and interact with them using emotional labor. The causes of emotional exhaustion under several circumstances have been thoroughly investigated. One approach is to view the employee-customer interaction as an actor-audience relationship, known as dramaturgy theory. From the dramaturgical perspective, this study examined how emotional labor influences emotional exhaustion and was moderated by four theatrical components: front-back stage division, job autonomy, customers' positive feedback, and explicitness of service scripts. Testing responses from a sample containing 271 employees from various service firms, this study showed that front-back stage division and job autonomy have a weakly moderating effect. Meanwhile, customers' positive feedback and explicitness of service scripts at different levels also possessed a distinct effect on the relationship between emotional labor and emotional exhaustion.
Keywords: L84; M31; M54; 330; Emotional labor; emotional exhaustion; dramaturgy theory; theatrical components; service marketing